x(x-10)=-34

Simple and best practice solution for x(x-10)=-34 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x-10)=-34 equation:


Simplifying
x(x + -10) = -34

Reorder the terms:
x(-10 + x) = -34
(-10 * x + x * x) = -34
(-10x + x2) = -34

Solving
-10x + x2 = -34

Solving for variable 'x'.

Reorder the terms:
34 + -10x + x2 = -34 + 34

Combine like terms: -34 + 34 = 0
34 + -10x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '-34' to each side of the equation.
34 + -10x + -34 + x2 = 0 + -34

Reorder the terms:
34 + -34 + -10x + x2 = 0 + -34

Combine like terms: 34 + -34 = 0
0 + -10x + x2 = 0 + -34
-10x + x2 = 0 + -34

Combine like terms: 0 + -34 = -34
-10x + x2 = -34

The x term is -10x.  Take half its coefficient (-5).
Square it (25) and add it to both sides.

Add '25' to each side of the equation.
-10x + 25 + x2 = -34 + 25

Reorder the terms:
25 + -10x + x2 = -34 + 25

Combine like terms: -34 + 25 = -9
25 + -10x + x2 = -9

Factor a perfect square on the left side:
(x + -5)(x + -5) = -9

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| -2(x-3)=2-(x+3) | | 3d^2+5d-6=0 | | -16=x+23 | | 5x=9-3 | | -5-2x=3-6 | | 21x+30=20-3 | | x-6=.66666666666666y | | -5x+6=-9x+22 | | 19+x=-16 | | 3p=4q+r | | 2(x-2)^1/4-3=159 | | 2x+31-2x+25-3x=2x-31+10-21x | | 3x+1.5=3+2 | | x-6=1/3y | | 21i+4i= | | X+2x+17=104 | | x-8.7=-4.4 | | 45m=9 | | 2(x-6)=6-(x+8)+4 | | A=10h | | 4x+5-5x=-7 | | z-3/10=27/10 | | 8-n^2-7n=0 | | x-12-8=-1 | | n^2-12n=-36 | | 0.8(y+3)=4.8 | | 2x(5/35) | | 2-5/13=6/7 | | 53x-y=-7 | | w-7/9=2/3 | | x+5x+-4=18+-2x | | -2z+3=-4z+11 |

Equations solver categories